Analysis of Revenue Recognition Practices in Trading Companies on The IDX: A Study of Compliance with Psak 115 - Zhaharah, Nur Azizaini (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2025)
This study aims to examine the implementation of revenue recognition practices in two large retail companies listed on the Indonesia Stock Exchange, namely PT Ramayana Lestari Sentosa Tbk and PT Matahari Department Store Tbk, and to assess the extent to which these practices are by the provisions of PSAK 115 concerning revenue from contracts with customers. This study uses a qualitative descriptive method, with data obtained through documentation from the official BEI website. The analysis is carried out based on five stages of revenue recognition under PSAK 115, namely contract determination, determining performance obligations, determining sales and purchase prices, allocating prices to obligations, and recognizing revenue. The results of the study indicate that both companies have implemented revenue recognition in general per PSAK 115, both in terms of direct sales and revenue from consignment goods and rental of business space.